A model of religious involvement, family processes, self-control, and juvenile delinquency in two-parent families. (February 2018) - Guo, Siying
Abstract: Family processes, adolescent religious involvement, and self-control may serve as important mechanisms that mediate the relationship between parental religious involvement and delinquency. However, at present no study has systematically investigated the relationships among these factors and how these mediating mechanisms work. To address this gap, path analyses are conducted to test the hypothesized pathways whereby parental religious involvement operates to discourage delinquent behaviors of offspring. The study variables are taken from three waves of the study of the National Longitudinal Survey of Youth 1979 and its descendent NLSY79 Child and Young Adults at two year intervals (2000, 2002, and 2004). 1020 American adolescents who are 10–14 years old in 2002 are selected for final analyses. The findings suggest that parental religious involvement does not affect adolescent delinquency four years later directly, but indirectly through its influence on adolescent religious involvement, parenting practices, inter-parental conflict, and their interactions with adolescent self-control.